Praktek perkawinan beda agama dihubungkan dengan undang-undang perkawinan dan putusan mahkamah konstitusi nomor 68 tahun 2014 - Faroha, Diar (ARKA INSTITUTE, 2022)
Marriage is the union of two people who initially live alone and then are united in the sacred bond of marriage, which then forms a family (household). Interfaith marriages often occur and many do it, but it is clear that religion forbids interfaith marriages and Article 2 paragraph 1 of the UUP also emphasizes that marriage must be based on each other's beliefs or religions. This type of research uses normative juridical research methods, namely legal research that prioritizes library research with an emphasis on reviews from a scientific perspective and how it is implemented in practice. Humans by nature are social creatures who cannot live alone and must coexist with each other, marriage bonds are legal bonds between men and women on the basis of love and affection between them. Therefore, humans always live with each other, the family is the smallest group in the structure of social life. As according to the decision of the Constitutional Court number 68 of 2014 that marriage must be based on religion and beliefs held by each individual.